Poverty and the prediction of health status in adolescents from low-income families in Taiwan. (4th January 2019) - Liang, Ya-Lun; Tsai, Meng-Che; Lin, Yi-Ching; Strong, Carol; Lin, Chung-Ying
ABSTRACT: Background: A comparison of the performance between monetary and an asset-based socioeconomic position (SEP) index in predicting adolescents' health outcomes was conducted only in low-income countries. Our study aims to compare these two indices among adolescents from low-income families in a high-income country. Methods: Data of adolescents aged 12–18 years was used from the Taiwan Database of Children and Youth in Poverty ( n = 2529). The asset-based index was based on a set of weighted self-reported household conditions using principal components analysis. Multivariable logistic regression was conducted to examine the association between these two indices and the mental and physical health outcomes among adolescents. Results: Health outcomes were significantly associated with the asset-based SEP index but not with the monetary index. An increased trend was shown in mental illness symptoms, infections, injuries, allergies and dental problems when the regression was performed in the asset-based SEP index ( P < 0.05) but not in the monetary SEP index. Conclusions: An asset-based SEP index serves as a better index associated with a social gradient in health inequality. To prioritize giving care to people in need, healthcare policymakers should consider including an assessment of household assets and resources, supplementary to the conventional monetary index.